2014
DOI: 10.1073/pnas.1404671111
|View full text |Cite
|
Sign up to set email alerts
|

Memory B cells contribute to rapid Bcl6 expression by memory follicular helper T cells

Abstract: In primary humoral responses, B-cell lymphoma 6 (Bcl6) is a master regulator of follicular helper T (T FH ) cell differentiation; however, its activation mechanisms and role in memory responses remain unclear. Here we demonstrate that survival of CXCR5 + T FH memory cells, and thus subsequent recall antibody response, require Bcl6 expression. Furthermore, we show that, upon rechallenge with soluble antigen Bcl6 in memory T FH cells is rapidly induced in a dendritic cell-independent manner and that peptide:clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 34 publications
3
75
1
1
Order By: Relevance
“…Either of these possibilities is intriguing, the latter because the maintenance of GC T cells by memory B cells has not been described in humans or mice previously. It has, however, been suggested that memory B cells are able to support lymph-node resident memory Tfh-like cells in mice, 56,57 raising the possibility that the Tfh cells identified in this study may represent a lymphoid reservoir of memory Tfh cells similar to those described in mice, 56 rather than a bona fide effector population. This seems unlikely, however, as CD57…”
Section: Cd4mentioning
confidence: 56%
“…Either of these possibilities is intriguing, the latter because the maintenance of GC T cells by memory B cells has not been described in humans or mice previously. It has, however, been suggested that memory B cells are able to support lymph-node resident memory Tfh-like cells in mice, 56,57 raising the possibility that the Tfh cells identified in this study may represent a lymphoid reservoir of memory Tfh cells similar to those described in mice, 56 rather than a bona fide effector population. This seems unlikely, however, as CD57…”
Section: Cd4mentioning
confidence: 56%
“…Bcl6 is essential for the induction of Tfh cell differentiation as the reciprocal repression of Bcl6 and BLIMP1 controls the development of Tfh vs. non‐Tfh CD4 + T helper cell populations (Johnston et al , 2009; Nurieva et al , 2009; Yu et al , 2009). At later stages, Bcl6 is required for stable Tfh effector commitment and the maintenance of memory Tfh cells (Liu et al , 2012; Ise et al , 2014). Still, the regulation of Bcl6 in the course of Tfh cell differentiation is incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“…All experiments used mice on a C57BL/6 background except where noted. BCL6 flox, IL-2 −/− , BLIMP-1 reporter, Foxp3 fusion protein DTR-GFP (FDG), Foxp3-Gfp eFox, and IL-21 reporter mice have already been described (45)(46)(47)(48)(49).…”
Section: Methodsmentioning
confidence: 99%